Pengaruh Media Memory Card terhadap Pengetahuan, Sikap dan Keterampilan Cuci Tangan Siswa SDN 016 Samarinda Ulu - Nanda Gista Maharani; Dwi Hendriani; Nino Adib Chifdillah; Nina Mardiana (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Handwashing with soap is a key clean and healthy behavior that plays an important role in preventing infectious diseases among school-aged children. However, the low levels of students’ knowledge, attitudes, and skills indicate the need for effective and engaging health education. One of the media that can be used is memory cards as an interactive educational tool. This study aimed to determine the effect of memory card media on knowledge, attitudes, and handwashing skills among elementary school students. The study employed a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of students from SDN 016 Samarinda Ulu, selected using a total sampling technique. Data were collected before and after the intervention using knowledge and attitude questionnaires, as well as an observation checklist for handwashing skills. Data analysis was conducted using the Wilcoxon test. The results showed a significant improvement in knowledge, attitudes, and skills after the intervention, with a p-value of 0.000 (p < 0.05). In conclusion, memory card media is effective in improving students’ knowledge, attitudes, and handwashing skills, and has the potential to serve as an interactive and relevant health education alternative in school settings.